Pengaruh Strategi Diskon Terhadap Keputusan Pembelian Konsumen Indomaret dan Alfamart Di Kawasan UNIMED - Ridho Syafrizal; Agnes Putri Farida Sitorus; Saufina Azzahra Zebua; Dhiyah Faliha Syahira; Qatrun Nada; Shezy Ratisya Dwina; Muhammad Ilyas Sapawi; Aprinawati (Universitas 45 Surabaya, 2024)
Indomaret and alfamart are retail stores that are often side by side and are always visited by many consumers every day to shop. This is an indication that there is something influencing their behavior to come back to these retail stores. This article explores the causes of the crowds of consumers who come every day at indomaret and alfamart based on the availability of discounts at the two retail stores. The purpose of this study is to determine whether consumers shop at these two retail stores because of discounts or there are other reasons that support this behavior. The author used a quantitative method with an observation and interview approach. The sample size was set at 50 customers, with details of 25 Alfamart and 25 Indomaret customers in the area around Medan State University. The results showed from the data collected that 34% of Indomaret or Alfamart visitors came to the retail store out of necessity. While coming because of a discount of 26% where this figure is below the first variable. This indicates that discounts do not have a significant effect on consumer purchasing behavior of indomaret and alfamart retail stores.